Rút gọn biểu thức sau :
12 + 3.y + 4.x + x.y - 12 + 2.y + 6.x - x - 5.y
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: \(P=\left(5x-1-5x-4\right)^2=\left(-3\right)^2=9\)
b: \(Q=\left(x+y\right)^3-3xy\left(x+y\right)=x^3+y^3\)
c: \(=\dfrac{\left(5^2-1\right)\left(5^2+1\right)\left(5^4+1\right)\left(5^8+1\right)\left(5^{16}+1\right)}{2}\)
\(=\dfrac{\left(5^4-1\right)\left(5^4+1\right)\left(5^8+1\right)\left(5^{16}+1\right)}{2}\)
\(=\dfrac{\left(5^8-1\right)\left(5^8+1\right)\left(5^{16}+1\right)}{2}\)
\(=\dfrac{5^{32}-1}{2}\)
Bài 2:
Đặt \(\dfrac{x}{3}=\dfrac{y}{4}=k\)
\(\Leftrightarrow\left\{{}\begin{matrix}x=3k\\y=4k\end{matrix}\right.\)
Ta có: xy=12
\(\Leftrightarrow12k^2=12\)
\(\Leftrightarrow k^2=1\)
Trường hợp 1: k=1
\(\Leftrightarrow\left\{{}\begin{matrix}x=3k=3\\y=4k=4\end{matrix}\right.\)
Trường hợp 2: k=-1
\(\Leftrightarrow\left\{{}\begin{matrix}x=3k=-3\\y=4k=-4\end{matrix}\right.\)
=\(\frac{2^{12}.3^5+2^{12}.3^4}{2^{12}.3^6+2^{12}.3^3}\)
=\(\frac{2^{12}\left(3^5+3^4\right)}{2^{12}\left(3^6+3^3\right)}\)
\(=\frac{324}{756}\)
=\(\frac{3}{7}\)
Lời giải:
$x=4$ thì $\frac{x}{2}=2=y$
$\Rightarrow y-\frac{x}{2}=0$
Do đó:
$(\frac{x}{2}-y^3)^3-6(y-\frac{x}{2})^2-12(y-\frac{x}{2})-8$
$=(\frac{x}{2}-y^3)^3-8=(2-2^3)^3-8=-224$
\(12+3y+4x+xy-12+2y+6x-x-5y\)
\(=9x+xy\)
\(=x\left(y+9\right)\)
12+3y+4x+xy-12+2y+6x-x-5y=
=9x+xy
=x(9+y)